The effect of human resource practices towards business performance in transportation companies in Malaysia - Zali, Nadhirah Illana; Saad, Mazni (2019)
Human Resource (HR) practices plays a vital role in a corporation as it helps the management of the corporation to run smoothly and minimize the problems and obstacles in the corporation. The primary objective of this study is to determine the correlation between HR practices, which are, training and development, recruitment and selection and performance appraisal, and business performance of transportation companies in Malaysia. Quantitative empirical with cross- sectional method were used. This study surveyed four types of transportation companies which are airlines, trains and busses with total respondents of 51 employees. The findings of the study revealed that HR practices are positively correlated to the business performance of transportation companies in Malaysia. The findings of the study have the potential to help anagement of the transportation companies in adapting proper and well-articulated HR practices in building human capital and stimulating the necessary behaviours that create an advantage for the organization.